Energy poverty and emerging debates: Beyond the traditional triangle of energy poverty drivers. (October 2022) - Stojilovska, Ana; Guyet, Rachel; Mahoney, Katherine; Gouveia, João Pedro; Castaño-Rosa, Raúl; Živčič, Lidija; Barbosa, Ricardo; Tkalec, Tomislav
Abstract: This paper evaluates whether, how, and why policy documents in six diverse European countries (Spain, France, Portugal, the UK, North Macedonia, and Slovenia) link energy poverty to other related policy areas. Our exploratory study suggests that the most explicit links to energy poverty are made in energy efficiency policies rather than in energy price and income policies, due to the dominant techno-economic approach to addressing energy poverty. As countries with a long tradition of addressing energy poverty, France and the UK integrate energy poverty to a greater extent in linked policies. Policy integration is reflected in EU efforts to include energy poverty in climate and energy policies. Emerging debates linked to energy poverty include good governance, citizens' agency, new energy services, and new threats from the energy transition. We argue that the spatial divide of energy poverty across Europe is more than a physical (infrastructural) divide. It is a policy (political) divide embedded in the economic and political space co-shaped by national path dependencies, such as the social welfare system, the energy market, the level of experience of dealing with energy poverty, and the influence of EU policies. These conditions determine the national policy integration efforts linked to energy poverty. Highlights: Energy efficiency policies have the most explicit links to energy poverty. Countries with past experience with energy poverty show greater policy integration. EU has aligned energy poverty policies with energy and climate policies. A set of conditions impact the policy integration efforts linked to energy poverty.